F(x) = -3x + 7
y = -3x + 7
x = -3y + 7
-3y + 7 = x
-3y = x - 7
y = -1/3x + 7/3
f^-1(x) = -1/3x + 7/3
Answer: A.
Step-by-step explanation:
If you were to use the substitution method to solve the following system, we need to write one of the equation to an <span>expression equivalent to y. Let us say the second equation, we write it as follows:
</span><span>6x – 3y = –3
-3y = -6x - 3
y = 2x + 1
We substitute the equation to the first given equation as follows:
</span><span>2x – 5y = –3
</span>2x – 5(2x + 1) = –3
2x - 10x - 5 = -3
-8x = 2
x = -1/4
y = 2(-1/4) + 1 = 1/2
9 is in the hundred thousands place, 8 is in the ten thousands place, 7 is in the thousands place, 1 is in the hundreds place, 6 is in the tens place, 4 is in the ones place.